Togo : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper discusses the assessment of economic activity in Togo in absence of quarterly GDP series. Togo collects about 40 macroeconomic indicators monthly that span a wide range of sectors of the economy. The selection of the variables for the economic activity index is conducted by finding the combination of variables. The indicators are aggregated into an index using a methodology used by the Conference Board. Then an economic activity index is constructed that effectively replicates the historical growth rates of real GDP in Togo. The selected index minimizes the deviations between the growth rates of the indicator and actual real GDP growth over 2002-13.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet